2007
DOI: 10.1002/mus.20810
|View full text |Cite
|
Sign up to set email alerts
|

Rat α‐ and γ‐motoneuron soma size and succinate dehydrogenase activity are independent of neuromuscular activity level

Abstract: The chronic level of neuromuscular activity, that is, activation and loading, strongly influences the morphological, metabolic, phenotypic, and physiological properties of skeletal muscles. The effects on the innervating motoneurons, however, are less established. We determined and compared the effects of 30 days of decreased activity (induced by a complete mid-thoracic spinal cord transection, ST) or near inactivity (induced by spinal cord isolation, SI) on the soma size and succinate dehydrogenase (SDH) acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 46 publications
1
10
1
Order By: Relevance
“…According to the size of soma diameter, the labeled motor neurons were divided into two classes: the large one (soma diameter > 25  μ m) or the small one (soma diameter ≤ 25  μ m), belonging to α and γ motor neurons, respectively [19]. The approximate 60 transverse sections from spinal cord were counted on every rat, resulting in a total of 136 AF488-CTB labeled motor neurons (BL40) and 174 AF594-CTB labeled motor neurons (GB30).…”
Section: Resultsmentioning
confidence: 99%
“…According to the size of soma diameter, the labeled motor neurons were divided into two classes: the large one (soma diameter > 25  μ m) or the small one (soma diameter ≤ 25  μ m), belonging to α and γ motor neurons, respectively [19]. The approximate 60 transverse sections from spinal cord were counted on every rat, resulting in a total of 136 AF488-CTB labeled motor neurons (BL40) and 174 AF594-CTB labeled motor neurons (GB30).…”
Section: Resultsmentioning
confidence: 99%
“…In the study of McHanwell and Biscoe (1981), the equivalent circle diameters of the soma ranged from 19 to 37 µm (mean ~26 µm; 32 µm in the motoneuron we labeled in Figure 1B). For comparison, in cat motoneurons, soma diameters ranged from 40 to 80 µm (mean ~50 µm; Burke et al, 1977; Ulfhake and Kellerth, 1984; Horcholle-Bossavit et al, 1988) whereas they ranged from 20 to 40 µm (mean 30 µm) in rats (Swett et al, 1986; Hashizume et al, 1988; Roy et al, 2007). Finally, Ishihara et al (2001) showed that the mean somatic diameter of soleus motoneurons was 26 µm in mice, 34 µm in rats, and 51 µm in cats.…”
Section: Discussionmentioning
confidence: 99%
“…A complete spinal cord transection at the T7–T8 level was performed as described previously (Talmadge et al, 2002). Spinal cord isolation was performed as previously described (Grossman et al, 1998; Roy et al, 2007a,b). Briefly, a partial laminectomy was performed between vertebral levels T7 and ~S1.…”
Section: Methodsmentioning
confidence: 99%